Diagnosis of double splenic artery pseudoaneurysm: CT scan versus angiography. (28th April 2015) - Badour, Sanaa; Mukherji, Deborah; Faraj, Walid; Haydar, Ali
Abstract : The formation of splenic artery pseudoaneurysms is a commonly reported complication of chronic pancreatitis. Angiography has an established role in the diagnosis of splenic artery pseudoaneurysms while CT scan is thought to be less accurate for making this diagnosis. In this report, we present a rare case of two separate concomitant splenic artery pseudoaneurysms, illustrating the value of combining CT and angiography for optimal visualisation and treatment.